Patterns of Rape in Metro Manila: A Sociological Analysis - Candaliza, Filomin A. (Review of Women's Studies; Vol 11 No 1-2 (2001): Review of Women's Studies Volume XI, Numbers 1-2 (January-December 2001), 2002)
---